FAKTOR-FAKTOR PENGHAMBAT LITERASI DI SD NEGERI 55/1 SRIDADI - Kurniawan, Agung Rimba; nelli, Destri; Hayati, Suci; Priyono, Adi; Roza, Kiki Dwilia; Nia, Melli; Waliyanti, Nopi (Universitas Negeri Malang, 2021)
Literacy is the ability to identify, create, interpret, communicate and count, and read in daily life in order to develop social, economic, and cultural potential in modern life so that it can become a quality and virtuous person. The purpose of writing this article is to find out what are the inhibiting factors of literacy in Sridadi 55 / I Elementary School. The method used uses a phenomenological approach to the type of case study. The results of this study are students at Sridadi 55 / I Elementary School already have a fairly good interest in reading, but the lack of reading books available in libraries and reading corners makes students less enthusiastic about reading.